Strain-modulated photoelectric responses from a flexible α-In₂Se₃/3R MoS₂ heterojunction - Cai, Weifan (2023)
Semiconducting piezoelectric α-In2Se3 and 3R MoS2 have attracted tremendous attention due to their unique electronic properties. Artificial van der Waals (vdWs) heterostructures constructed with α-In2Se3 and 3R MoS2 flakes have shown promising applications in optoelectronics and photocatalysis. Here, we present the first flexible α-In2Se3/3R MoS2 vdWs p-n heterojunction devices for photodetection from the visible to near infrared region. These heterojunction devices exhibit an ultrahigh photoresponsivity of 2.9 × 103 A W-1 and a substantial specific detectivity of 6.2 × 1010 Jones under a compressive strain of - 0.26%. The photocurrent can be increased by 64% under a tensile strain of + 0.35%, due to the heterojunction energy band modulation by piezoelectric polarization charges at the heterojunction interface. This work demonstrates a feasible approach to enhancement of α-In2Se3/3R MoS2 photoelectric response through an appropriate mechanical stimulus.